Cooperative consolidation of enterprises rescued by their workers in Argentina and Uruguay - Julián Rebón; Instituto de Investigaciones Gino Germani, UBA; Anabel Rieiro Castiñeira; Departamento de Sociología, FCS, Udelar y ANII (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2020)
Companies recovered by their workers have gained increasing recognition at international level. Argentina and Uruguay represent territories from which these processes reached greater development since the crisis at the beginning of the century. In the search for understanding the transformations that these groups have been able to sustain and consolidate over time, in this article we investigate the positive factors for their consolidation. The methodological strategy is based on the comparative analysis of two recovered enterprises that have achieved cooperative consolidation, one located in Argentina and the other in Uruguay. Some of the main factors positively evaluated in both cases were: the participation and construction of different socio-political and cultural frameworks, the resources inherited from the failed enterprise, the hegemony of a multidimensional collective project that, starting from self-management, seeks to achieve an economically and socially viable project, the legal possession of the means of production and access to credit, as well as the production of commercially competitive goods and services in a framework of pluralistic economic exchanges.